Enhanced removal of sulfonamide antibiotics by KOH-activated anthracite coal: Batch and fixed-bed studies. (April 2016) - Zuo, Linzi; Ai, Jing; Fu, Heyun; Chen, Wei; Zheng, Shourong; Xu, Zhaoyi; Zhu, Dongqiang
Abstract: The presence of sulfonamide antibiotics in aquatic environments poses potential risks to human health and ecosystems. In the present study, a highly porous activated carbon was prepared by KOH activation of an anthracite coal (Anth-KOH), and its adsorption properties toward two sulfonamides (sulfamethoxazole and sulfapyridine) and three smaller-sized monoaromatics (phenol, 4-nitrophenol and 1, 3-dinitrobenzene) were examined in both batch and fixed-bed adsorption experiments to probe the interplay between adsorbate molecular size and adsorbent pore structure. A commercial powder microporous activated carbon (PAC) and a commercial mesoporous carbon (CMK-3) possessing distinct pore properties were included as comparative adsorbents. Among the three adsorbents Anth-KOH exhibited the largest adsorption capacities for all test adsorbates (especially the two sulfonamides) in both batch mode and fixed-bed mode. After being normalized by the adsorbent surface area, the batch adsorption isotherms of sulfonamides on PAC and Anth-KOH were displaced upward relative to the isotherms on CMK-3, likely due to the micropore-filling effect facilitated by the microporosity of adsorbents. In the fixed-bed mode, the surface area-normalized adsorption capacities of Anth-KOH for sulfonamides were close to that of CMK-3, and higher than that of PAC. The irregular, closed micropores of PAC might impede the diffusion of the relatively large-sized sulfonamide molecules and in turn led to lowered fixed-bed adsorption capacities. The overall superior adsorption of sulfonamides on Anth-KOH can be attributed to its large specific surface area (2514 m 2 /g), high pore volume (1.23 cm 3 /g) and large micropore sizes (centered at 2.0 nm). These findings imply that KOH-activated anthracite coal is a promising adsorbent for the removal of sulfonamide antibiotics from aqueous solution. Highlights: A high efficiency adsorbent for sulfonamide removal is prepared from anthracite. Effects of adsorbent porosity are studied in both batch mode and fixed-bed mode. KOH-activated anthracite shows high adsorption for sulfonamides in both modes. The micropores of activated carbon impede fixed-bed adsorption of sulfonamides. Abstract : The large specific surface area, high pore volume and enlarged micropores make KOH-activated anthracite coal a superior adsorbent for sulfonamides.